The New Age of Sudomotor Function Testing: A Sensitive and Specific Biomarker for Diagnosis, Estimation of Severity, Monitoring Progression, and Regression in Response to Intervention - Vinik, Aaron I.; Nevoret, Marie-Laure; Casellini, Carolina (Frontiers in Endocrinology, 2015)
Sudorimetry technology has evolved dramatically, as a rapid, non-invasive, robust, and accurate biomarker for small fibers that can easily be integrated into clinical practice. Though skin biopsy with quantitation of intraepidermal nerve fiber density (IENFD) is still currently recognized as the gold standard in the evaluation, sudorimetry may yield diagnostic information not only on autonomic dysfunction, but also enhance the assessment of the small somatosensory nerves, disease detection, progression, and response to therapy. Sudoscan is based on different electrochemical principles (reverse iontophoresis and chronoamperometry) to measure sudomotor function than prior technologies, affording it a much more practical and precise performance profile for routine clinical use with potential as a research tool. Small nerve fiber dysfunction has been found to occur early in metabolic syndrome and diabetes and may also be the only neurological manifestation in small fiber neuropathies, beneath the detection limits of traditional nerve function tests. Test results are robust, accomplished within minutes, require little technical training, no calculations since established norms have been provided for the effects of age, gender and ethnicity. Sudomotor testing has been greatly under-utilized in the past, restricted to specialist centers capable of handling the technically demanding, invasive biopsies for quantitation of IENF and expensive technology. Yet evaluation of autonomic and somatic nerve function has been shown to be the single best estimate of cardiovascular risk. Evaluation of sweating has the appeal of quantifiable non–invasive determination of the integrity of the peripheral autonomic nervous system, and can now be accomplished with the Sudoscan™ tool rapidly at point of care clinics, allowing intervention for morbid complications prior to permanent structural nerve damage. We review here sudomotor function testing technology; the research evidence accumula